Impact of COVID-19 on the Psychological Well-Being of HealthCare Workers in India: A Systematic Review and Meta-analysis - Sujatha Shanmugasundaram; Elizabeth Halcomb; Elizabeth Bembridge; Marlen Orsina; Sarah Turner; Ritin Fernandez (Indian Journal of Psychiatric Nursing)
This review aimed to synthesize the impact of COVID-19 on healthcare workers (HCWs) psychological well-being in India. During the COVID-19 pandemic, HCWs internationally experienced significant negative psychological impacts. India has been particularly affected due to its limited resources, health workforce challenges, and financial constraints. Learning from the impacts of COVID-19 is important to promote strategies to support the healthcare workforce in future pandemics. A systematic review and meta-analysis were undertaken. Papers were identified from a systematic search of electronic databases from January 2020 to June 2022. Papers were included if they were published in the English language and reported the psychological well-being of HCWs in India during the COVID-19 pandemic. Of the 20 papers included in the review, 19 described cross-sectional studies and one study used mixed methods. The overall prevalence of anxiety among all HCWs was 35.8% (95% confidence interval [CI] 23.2%, 49.4%). Interestingly, the subgroup analysis reported the prevalence of anxiety among other HCWs (27%) rather than doctors (26.8%) or nurses (29.2%). The prevalence of depression among all HCWs was 35.1% (95% CI 23.4%, 47.8%). Subgroup analysis demonstrated that the prevalence of depression was highest among other HCWs (40.3%) compared to nurses (32.8%) and doctors (26.9%). The prevalence of stress among all HCWs was 71.5% (95% CI 48.5%, 89.8%). A subgroup analysis demonstrated that the prevalence of stress was highest among doctors (70.9%), followed by other HCWs (52.3%) and lowest among nurses (38.8%). Based on the meta-analysis of all the articles included, there was a significant positive correlation between the prevalence of anxiety, depression, and stress with age, gender, and marital status. This systematic review demonstrates the significant pandemic impacts on the psychological well-being of HCWs in India. Understanding the differences in psychological impacts between different HCWs and associated demographic factors is important in informing interventions for future pandemic management. Providing evidence-based, comprehensive support for HCWs is crucial to safeguard their psychological well-being and promote workforce capacity during pandemic conditions.